Clinical features of Bednar's aphthae in infants - Seung-Woo Nam; Seol Hee Ahn; Son-Moon Shin; Goun Jeong (Korean Pediatric Society, 2016)
PurposeAlthough Bednar's aphthae are common and regress spontaneously, these lesions may lead to feeding intolerance and are often misdiagnosed, rendering examinations useless. This study sheds new light on the clinical features of Bednar's aphthae.MethodsSixteen neonates and infants were newly diagnosed with Bednar's aphthae via routine health check-ups in an outpatient clinic. Medical records were retrospectively reviewed, and the following parameters were analyzed; sex, gestational age, birth weight, mode of delivery, and perinatal problems. A physical examination was carried out during the next outpatient visit to examine the healing process and check for the existence of scars or complications.ResultsInitial presentation included changes in feeding habits (n=10), longer feeding time, reduced intake, and increased irritability. In 6 patients, Bednar's aphthae were discovered incidentally, without prior symptoms. Feeding posture and method of feeding are important causes of Bednar's aphthae. Eleven patients were fed in a horizontal position, whereas 5 patients were fed in a semiseated position. Fifteen patients were bottle-fed, whereas 1 patient was exclusively breastfed. After correcting the feeding position, the ulcerative lesions disappeared within 1 month of diagnosis. During the follow-up period, lesions did not recur in any of the patients.ConclusionThis study suggests that Bednar's aphthae are caused by mechanical pressure. A diagnosis of Bednar's aphthae should be considered when lesions are found on the palate of infants and when symptoms seem to be feeding related. Proper education of parents can both treat Bednar's aphthae and easily prevent its recurrence.